If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(x+9)-19=-7
We move all terms to the left:
6(x+9)-19-(-7)=0
We add all the numbers together, and all the variables
6(x+9)-12=0
We multiply parentheses
6x+54-12=0
We add all the numbers together, and all the variables
6x+42=0
We move all terms containing x to the left, all other terms to the right
6x=-42
x=-42/6
x=-7
| 8x+3÷2=3x-4 | | -115=-3-7x | | 6(x+13)+14=152 | | 2(x+3)+13=5 | | x2+-9x=-19 | | -7-5x=6x-4 | | 8(x+12)-14=162 | | -72=8-4x | | 10(x+2)+20=0 | | -13=-x+1 | | 12d+16=-100 | | -8-4x=60 | | 5x+2=-2x+33 | | -41=7-3x | | 5(x+7)-12=-22 | | y-49/9=4 | | 12b+16=-100 | | -3-7x=-115 | | 490,5x=390 | | 2/3(m+4)=1/3(4m+12) | | 4(-7x-1)=80 | | 5=t/2+4 | | 8(x+5)+6=102 | | 4t+12=20 | | 3(x-6)-20=-20 | | 490.5x=390 | | 2a+17=6a-15 | | 8(x+5)+8=-16 | | 6(x+13)=18 | | 14=t/3+10 | | 8e+2=10 | | 9(x+11)=81 |